Perbedaan PaCO2 darah pada pasien kritis yang mendapat diet makanan enteral komersial dengan diet makanan enteral kombinasi di rumah sakit Dr. Sardjito Yogyakarta - M Jaelani; Untung Widodo; Susetyowati Susetyowati (Jurnal Gizi Klinik Indonesia, 2006)
Background: Malnutrition often occurs in a critical patient caused by various things such as decreasing function of gastrointestinal tract, high process of catabolism and homeostatie destruction. Other problem that may occur when nutrition is given with high total calories could be dangerous because it could cause hiperglikemia, the production improvement of CO blood and worsen the homeostasis destruction.Objective: To find out the difference of PaCO blood in critical patients who obtain commercial enteral food diet or combined enteral food diet.Methods: This was an experimental study using randomized controlled trial with pretest-posttest control group design. The subjects were critical patients who were given care in the intensive installation Dr. Sardjito hospital Yogyakarta who met the criteria: adult patient, using ventilator and receiving enteral food diet.Results: There was no difference between PaCO blood in critical patient who obtained commercial enteral diet and com- bined enteral food diet. There was a change difference of PaCO with <80% from total energy (p=0.03) and there was a different on change of PaCO in carbohydrate intake between criteria >55% compared with <55% from energy total (p=0.03).Conclusion: The improvement of PaCO was not caused by the type of enteral formula given, cause of the high intake of energy and carbohydrate.